METODE âBACKWARD CHAININGâ DALAM PENGAJARAN KETERAMPILAN MENGURUS DIRI SENDIRI PADA ANAK IMBESIL - Pristiwaluyo, Triyanto (Pendidikan Luar Biasa, 2012)
Abstract; The research was aimed at finding out effectiveness of backward chaining method in teaching self managenet skills, especially in putting on T-shirt skills to the  imbeciles of elementary level. The research objects incvluded imbeciles student of elementary level III of special scholls “C” in Makassar City.The research applied an exceptional method with Posttest Only Control Design. The research has two group, experiment and control group.The treatment was self management skill exercises, especially putting on T-shirt excercises using backward chaining method. Data collection was conducted through the direct observation to the students performance in doing the tasks given, especially in putting on T-shirts.The result of research show the existence of difference of efficacy of child of imbecil elementary class three in special scholls “C” Makassar City in putting on T-shirt among the student was trained using backward chaining method with conventional method. This matter indicate that there is influence of applying of backward chaining method to ability in putting on T-shirt of imbecil elementary levels in special scholls “C” Makassar City, so that can be used as an alternative method  in the teaching of self management skills to the imbeciles.